Efficacy of the cervical extension vibrating apparatus in the treatment of patients with cervical spondylosis - Gieremek, K; Saulicz, E; Pilat, A; Molicka, D (Cuestiones de Fisioterapia, 2003)
The examinations included 68 persons with discopathy and/or spondyloartrosis diagnosis of the neck-section of the spine, and among whom the presence of a brachial neuralgia on different intensity levels. From amongst the tested, two groups were formed: a 34 experimental group and a 34-control group. Patients from the experimental group, besides a therapy consisting of typical physiotherapeutic treatment program were additionally introduced to a originally constructed Glisson type cervical tractor with a built-in mechanism for emitting mechanical vibracions. The traction with a constant force additionally enriched by a vibratory massage with frequency up to 100 Hz and amplitude 0,2 mm.Close and distant effects of therapy in both tested groups were judged on the basis of a series of object tests with a special regard towards mobility indicators and pain symptoms.The results indicate that the vibratory cervical traction is well tolerated by patients with neck spondylosis and gives measurable therapeutic results.